Peddling on buses: the buscas in the city of Buenos Aires, Argentina - Perelman, Mariano D. (Tempo Social, 2017)
During a bus ride, a vendor might embark to offer a product. When this happens, a scene takes place in front of the passenger: a man steps on the bus, says some words to the bus driver and starts a performance more or less known to any frequent passenger. However, in order for this scene to take place, a number of relations allowing vendors to enter and remain in their activities in the bus are necessary. This article advances in this terrain. Based on an ongoing field work with street vendors working in public transportation within the reaches of the city of Buenos Aires,the text centers on how vendors create and keep relations with other actors, building a territory, a socially constructed space, in order to perform their activities.